2017
DOI: 10.2174/1874372201711010012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dietary Supplementation in the Treatment of Vitiligo

Abstract: Background:Vitiligo is the most common acquired pigmentary disorder in the world. Due to alterations in physical appearance, vitiligo is a psychologically devastating disease. Although treatment options exist, a cure for this disease has yet to be discovered. Of recent interest in vitiligo is the relationship between diet and disease. Objective:To review various dietary modifications and supplementation used in the management of vitiligo. Materials and Methods:A thorough evaluation of recent literature using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…An increase in the number of circulating CD8+ lymphocytes that are reactive to Melan-A/Mart-1 (a melanoma antigen recognized by T cells), glycoprotein 100 (gp100), and tyrosinase. Activated CD8+ cells can be found in the skin around vitiligo lesions [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the number of circulating CD8+ lymphocytes that are reactive to Melan-A/Mart-1 (a melanoma antigen recognized by T cells), glycoprotein 100 (gp100), and tyrosinase. Activated CD8+ cells can be found in the skin around vitiligo lesions [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that melanocytes degeneration and lower melanin biosynthesis in vitiligo patients may result in increased serum Cu and Zn levels. Hence, the high serum levels of these elements in vitiligo are the result of the disease rather than its underlying cause [25]. Several other studies have reported significantly decreased serum levels of Cu and/or Zn among vitiligo patients [21,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, more than 90% of vitamin D which is powerful antioxidant is formed after the body is exposed to sunlight. [14,15]. In vitiligo, Rathore et al [16] revealed substantial improvement in CAT and SOD activity after oral antioxidants and NB-UVB phototherapy.…”
Section: Introductionmentioning
confidence: 99%